Filtration of Active Components with Antioxidant Activity Based on the Differing Antioxidant Abilities of Schisandrae Sphenantherae Fructus and Schisandrae Chinensis Fructus through UPLC/MS Coupling with Network Pharmacology - Yang Xin (Evidence-Based Complementary and Alternative Medicine, 2021)
This study attempted to filter active components with antioxidant activities based on the differing antioxidant abilities of Schisandrae Sphenantherae Fructus (SSF) and Schisandrae Chinensis Fructus (SCF). First, the antioxidant activity of SSF and SCF was evaluated through the DPPH free radical scavenging method and compared with the half maximal inhibitory concentration (IC50) value. Next, components of SSF and SCF were detected by employing ultrahigh-performance liquid chromatography-Q-Exactive Orbitrap mass spectrometry (UPLC-QEO/MS) technology, and differential compounds were screened out as potential antioxidant compounds by using Compound Discover 3.1 Software. After that step, in order to verify the antioxidant compounds, the network method was applied. Biological targets were searched in the GeneCards database, and that related to antioxidant ability were selected in the Comparative Toxicogenomics Database (CTD). Finally, the pharmacology network was constructed. Results showed that SSF and SCF possessed different compounds and antioxidant abilities. A total of 14 differential compounds such as γ-schizandrin, schisandrin B, schisandrin, and tigloylgomisin H between them were screened out and identified. Twenty targets associated with antioxidant activity contained MAP2K1, MAPK8, RPS6KB1, PRKCB, HIF1A, and so on were investigated. Thirty-six pathways contained HIF-1 signaling pathways, choline metabolism in cancer, serotonergic synapse, Fc epsilon RI signaling pathway, GnRH signaling pathway, and so on related to the above twenty targets were identified. The pharmacology network analysis indicated that the differential components may be helpful in treating various diseases, especially cancer, by exerting antioxidant activity. In conclusion, this study provided a novel method for identifying active components with antioxidant activity in SSF and SCF, and this method may be applicable for the filtration of bioactive components in other herbs.